2021
DOI: 10.1039/d0ta12472a
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of photocatalytic reactions on CuxO@TiO2 core–shell photocatalysts

Abstract: Titania (titanium(IV) oxide) is highly active, stable, cheap and abundant photocatalyst, and thus commonly applied in various environmental applications. However, two main shortcomings of titania, i.e., charge carriers’ recombination and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 59 publications
(70 reference statements)
0
27
0
Order By: Relevance
“…In addition, the most active titania, i.e., that used in a particulate form, cannot be easily recycled, as already discussed in the introduction. Accordingly, various methods of titania modification, doping, coupling, and immobilizing have been proposed to improve its photocatalytic performance [14,[90][91][92][93][94]. Ferrites have also been proposed as titania modifiers for three main purposes, i.e., (i) improved activity by hindering the charge carriers' recombination, (ii) extension of activity towards vis range of solar spectrum, and (iii) easy and cheap recycling, as presented in this Section.…”
Section: Tio 2 -Based Magnetic Photocatalystsmentioning
confidence: 99%
“…In addition, the most active titania, i.e., that used in a particulate form, cannot be easily recycled, as already discussed in the introduction. Accordingly, various methods of titania modification, doping, coupling, and immobilizing have been proposed to improve its photocatalytic performance [14,[90][91][92][93][94]. Ferrites have also been proposed as titania modifiers for three main purposes, i.e., (i) improved activity by hindering the charge carriers' recombination, (ii) extension of activity towards vis range of solar spectrum, and (iii) easy and cheap recycling, as presented in this Section.…”
Section: Tio 2 -Based Magnetic Photocatalystsmentioning
confidence: 99%
“…It should be mentioned, that H 2 evolution (or even overall water splitting) was firstly, carried out only under UV irradiation, as pristine titania is inactive under vis irradiation. Then, modified titania (via doping or surface modifications), e.g., with nonmetals [53,54], metals [55,56], and by coupling with other materials [57], has been applied. Interestingly, it has also been found that noble metals could be used for titania activation towards vis response because of plasmonic properties ("plasmonic photocatalysts") [58][59][60][61].…”
Section: Zero-dimension (0d) Photocatalystsmentioning
confidence: 99%
“…Unfortunately, similar to other plasmonic photocatalysts, though vis activity has been observed for oxidative decomposition of phenol, negligible evolution of hydrogen has been noticed under vis irradiation. An interesting approach has been designed by Wang et al for coreshell Cu x O@TiO 2 formation by microemulsion method [57]. It is well known that coupled oxides, such as titania and copper/silver oxides-despite their enhanced activity under UV irradiation due to the inhibition of charge recombination (either via heterojunction type II or Z-scheme mechanism [84])-are often not stable under irradiation in contrast to titania, as these oxides with a narrower bandgap suffer from photocorrosion [85][86][87].…”
Section: Zero-dimension (0d) Photocatalystsmentioning
confidence: 99%
See 2 more Smart Citations